Comparison of bronchial hygiene techniques in mechanically ventilated patients: a randomized clinical trial - Naue, Wagner da Silva (Rev Bras Ter Intensiva, 2019)
OBJECTIVE: To compare the effects of vibrocompression and hyperinflation with mechanical ventilator techniques alone and in combination (hyperinflation with mechanical ventilator + vibrocompression) on the amount of aspirated secretion and the change in hemodynamic and pulmonary parameters. METHODS: A randomized clinical trial with critically ill patients on mechanical ventilation conducted in the intensive care unit of a university hospital. The patients were randomly allocated to receive one of the bronchial hygiene techniques for 10 minutes (vibrocompression or hyperinflation with mechanical ventilator or hyperinflation with mechanical ventilator + vibrocompression). Afterwards, the patients were again randomly allocated to receive either the previous randomly allocated technique or only tracheal aspiration. The weight of aspirated secretions (in grams), ventilatory mechanics and cardiopulmonary data before and after the application of the techniques were analyzed. The tracheal reintubation frequency and time and mortality on mechanical ventilation were also evaluated. RESULTS: A total of 93 patients (29 vibrocompression, 32 hyperinflation with mechanical ventilator and 32 hyperinflation with mechanical ventilator + vibrocompression) on mechanical ventilation for more than 24 hours were included. The hyperinflation with mechanical ventilator + vibrocompression group was the only one that presented a significant increase in aspirated secretions compared to tracheal aspiration alone [0.7g (0.1 - 2.5g) versus 0.2g (0.0 - 0.6g), p value = 0.006]. CONCLUSION: Compared to tracheal aspiration alone, the combination of hyperinflation with mechanical ventilator + vibrocompression techniques was most efficient for increasing the amount of aspirated secretions.